1989
DOI: 10.1007/bf01739739
|View full text |Cite
|
Sign up to set email alerts
|

Release of saccades in schizophrenics: Inattention or inefficiency?

Abstract: This paper attempts to distinguish between inattention and inefficiency as the cause of the eye movement problems of schizophrenic subjects. It focuses on their release of fast saccadic eye movements in four different situations: interrupting smooth tracking, as double-jumps in refixation, and as inadvertent departures from steady fixation or too-early prediction moves. If an attention deficit causes saccades during tracking, they should be reduced only for schizophrenic subjects in the dark, when there is no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
0
10
1
1
Order By: Relevance
“…The absence of a difference in gain between affective disorder patients and controls in the present study is consistent with the report of Mather et al (1989), but is not consistent with the report of Yee et al (1987). As noted above, tracking of our stimulus probably demanded less sustained attention and less velocity matching capacity in the smooth pursuit system than most studies, including that of Yee et al (1987).…”
Section: Schizophrenics R Controlscontrasting
confidence: 56%
See 1 more Smart Citation
“…The absence of a difference in gain between affective disorder patients and controls in the present study is consistent with the report of Mather et al (1989), but is not consistent with the report of Yee et al (1987). As noted above, tracking of our stimulus probably demanded less sustained attention and less velocity matching capacity in the smooth pursuit system than most studies, including that of Yee et al (1987).…”
Section: Schizophrenics R Controlscontrasting
confidence: 56%
“…Studies comparing patients with affective disorders and normal controls have generally indicated that these patients track abnormally (global measures: Shagass et al 1974;Lipton et al 1980;Levin et al 1981;Holzman et al 1984;Kufferle et al 1990;Amador et al 1991; for unipolar depression only: Iacono et al 1992; and for specific quantitative measures: Yee et al 1987;Abel et al 1991;Friedman etal.l 992 b) although exceptions exist (global measures: Cegalis & Sweeney, 1981;Iacono et al 1982Iacono et al , 1992; and specific quantitative measures: Abel et al 1991;Friedman et al \992b). Studies comparing patients with affective disorders to patients with schizophrenia have generally not found significant differences (global measures: Lipton et al 1980;Levin et al 1981;Holzman et al 1984;Solomon et al 1987;Kufferle et al 1990;Amador et al 1991;Iacono et al 1992; for bipolars in remission only: Iacono et al 1982; and for specific quantitative measures: Yee et al 1987;Mather et al 1989;Abel et al 1991;Friedman et al 19926), although here again, several exceptions exist (global measures: Cegalis & Sweeney, 1981;Iacono et al 1982;Iacono & Koenig, 1983).…”
Section: Introductionmentioning
confidence: 84%
“…Convergent lines of support for this expression of deficit have included connectionist modeling of schizophrenia processing of facial affect, where the subprocess-transaction rate has been computationally distinguished from the subprocess amount ; stochastic modeling of the speed and content of multidimensional similarity judgments, where group inequality in subprocess number has been integrated with Chechile's (1987) theory of memory-trace susceptibility (Carter & Neufeld, 1999); and various behavioral observations, including those bearing on eye-movement dysfunction, a much studied abnormality in schizophrenia (Mather, Neufeld, Russell, and Merskey (1989), Mather, Neufeld, Merskey, and Russell (1992), Neufeld, Mather, Merskey, and Russell (1995) and Neufeld and Williamson (1996); cf. Shelhamer (2008)).…”
Section: Discussionmentioning
confidence: 99%
“…5,6,25,26,30,32,36,37 Increased CUS rates in the predictive oscillating task are also consistent with earlier reports. 27,28,30,49,50 Unimpaired initial CUS accuracy in the step ramp task suggests that CUS efficiently corrected for small position errors when tracking moving targets. The presence of increased CUS rates together with unimpaired maintenance gain in the oscillating task might be explained by an instability of the pursuit response, resulting in increased aggregate CUS rates due to brief periods of slow pursuit rather than consistently slowed pursuit maintenance velocity.…”
Section: Commentmentioning
confidence: 99%